Predictability and Resetting in a Case of Convulsive Status Epilepticus - Hutson, Timothy; Pizarro, Diana; Pati, Sandipan; Iasemidis, Leon D. (Frontiers in Neurology, 2018)
In this case study, we present evidence of resetting of brain dynamics following convulsive status epilepticus (SE) that was treated successfully with anti-epileptic medications (AEDs). The measure of effective inflow (EI), a novel measure of network connectivity, was applied to the recorded intracranial multi-channel SEEG before, during and after SE. Results from this analysis indicate trends of progressive reduction of EI over hours up to the onset of SE, mainly at sites of the epileptogenic focus with reversal of those trends upon successful treatment of SE by AEDs. The proposed analytical framework is promising for elucidation of the pathology of neuronal network dynamics that could lead to SE, evaluation of the efficacy of SE treatment strategies, as well as the development of biomarkers for susceptibility to SE.